Improving School Safety in the District of Columbia: Evaluating the Safe School Certification Program, 2016-2020 - Temkin, Deborah ([Verlag nicht ermittelbar], 2022)
From 2016 through 2020, Child Trends, in partnership with the D.C. Office of Human Rights and the D.C. Office of the State Superintendent of Education, and with funding from the National Institute of Justice's Comprehensive School Safety Initiative, implemented and evaluated the Safe School Certification (SSC) Program, a three-year technical assistance model to support schools in strengthening organizational capacity across eight elements key to improving school climate: leadership, data, buy-in, policy and policy enforcement, student engagement, family and community engagement, training, and programs and practices. To help support schools' efforts, and to evaluate SSC's effectiveness, survey data were collected annually from students, parents, instructional staff, and non-instructional staff at participating schools using the U.S. Department of Education's School Climate Survey (EDSCLS), which was adapted to include measures of sexual orientation and gender identity, grit, and personal experiences of bullying and fights. Additionally, observations using the Classroom Assessment Scoring System - Secondary (CLASS-S) were conducted in a random sample of five classrooms in each participating school each year. Finally, as part of the implementation evaluation, interviews were conducted with the technical assistance providers, points of contact or leadership at participating schools, the SSC developer, and the manager of the Certification Advisory Board (CAB), which provided feedback to schools over the course of implementation through reviews of compiled workbooks.